SHAPING DISEASE: COLONIAL STIGMA AND THE POLITICS OF HEALTH IN BANYUWANGI, THE EARLY TWENTIETH CENTURY - Rifa'i Shodiq Fathoni (Paradigma: Jurnal Kajian Budaya, 2026)
This article examines the colonial stigma attached to Banyuwangi as an “unhealthy region” during the early 20th century, a label used to justify the extensive exploitation of its natural resources. Utilizing a historical methodology, this research examines how such stigma not only functioned as a tool for colonial legitimation but also causally contributed to conditions that precipitated ecological disasters and a public health crisis in what was previously an isolated area. Through an analysis of primary sources, including colonial reports, health journals, and newspapers, this study traces the manner in which large- scale plantation exploitation, enabled by the stigma, resulted in deforestation, uncontrolled labor migration, and poor sanitation in settlements. The findings suggest that the combined effects of environmental degradation and substandard living conditions fostered an ideal environment for the outbreak of tropical disease epidemics such as malaria and cholera, diseases that were not previously prevalent in Banyuwangi. Ironically, the colonial administration attributed these health issues to the lifestyles of local and migrant populations, rather than acknowledging the influence of its own policies. Furthermore, the study reveals that efforts to improve health conditions and eliminate stigma during the late 1920s, such as providing clean water, eradicating mosquito breeding sites, and modernizing health facilities, were undertaken only after the stigma had detrimental effects and began to hinder colonial economic interests. Consequently, this research concludes that the health crisis in Banyuwangi was a direct consequence of exploitative policies rooted in stigma, demonstrating the complex relationship between colonial narratives, environmental destruction, and public health in peripheral regions.